The Impact of Resilience and Extraversion on Psychological Distress, Loneliness, and Boredom During the COVID-19 Pandemic: A Follow-Up Study Among the General Population of Tyrol, Austria - Tutzer, Franziska; Frajo-Apor, Beatrice; Pardeller, Silvia; Plattner, Barbara; Chernova, Anna; Haring, Christian; Holzner, Bernhard; Kemmler, Georg; Marksteiner, Josef; Miller, Carl; Schmidt, Martin; Sperner-Unterweger, Barbara; et al. (Frontiers in Psychiatry, 2021)
Background: The Covid-19 pandemic and related measures represent an enormous burden on mental health. The aim of this study was to investigate longitudinal changes in psychological distress, loneliness, boredom, and resilience over the course of the pandemic and to examine the associations between resilience and extraversion at baseline (summer 2020) and psychological distress, loneliness, and boredom at 5-month-follow-up. Methods: Residents of Tyrol (≥18a) completed an online survey on psychological distress, loneliness, boredom, resilience, and extraversion by using the Brief-Symptom-Checklist, the Three-Item Loneliness Scale, the Multidimensional State Boredom Scale-Short Form, the Resilience Scale, and the Extraversion subscale of the Big 5 Inventory. Results: Of the 961 baseline participants, 384 took part in the follow-up survey. The percentage of study participants with striking psychological distress remained the same. Similarly, resilience did not change from baseline to follow-up, whereas the number of those experiencing moderate loneliness increased significantly. In contrast, at follow-up, severe loneliness was detected in significantly less people. Boredom decreased significantly over time. A moderate negative association was detected between baseline resilience and psychological distress, loneliness, and boredom at follow-up, and a weak but still significant negative association between extraversion and these outcomes. Discussion: These findings indicate that a subset of the general population consistently suffers from high levels of psychological distress and point to the protective effects of resilience and extraversion in this context. They reemphasize the importance of prevention and mitigation strategies to address these public health problems.